Pengembangan Modul Sistem Koloid Konteks "Pengolahan Limbah Batik" menggunakan Metode Four Steps Teaching Material Development - Firli Nurpatihah S; Sjaeful Anwar; Ijang Rohman (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a contextual colloidal system module with a batik wastewater treatment context that is suitable for senior high school students. The development of this module is motivated by the widespread use of teaching materials that do not fully align with curriculum demands, focusing solely on scientific content without applying a contextual approach. The research method employed is Design Development Evaluation (DDE), while the development of the teaching material follows the Four Steps Teaching Material Development (4STMD) model. In the design stage, analysis and planning of the type of teaching material to be developed were conducted, resulting in an initial draft of the module. The development stage, based on 4STMD, consists of four steps: selection, structuring, characterization, and didactic reduction, leading to the creation of a draft teaching material. The evaluation stage involved feasibility testing by chemistry teachers and experts, and comprehensibility testing with students. The evaluation results indicate that the developed contextual teaching material, based on the batik wastewater treatment context, is aligned with the curriculum, conceptually accurate, and feasible for use as independent learning material. The feasibility test yielded a percentage score of 95.4%, and the comprehensibility test yielded a score of 92%.